*Answer :*

**Concept Used:**

Factor theorem: If (x – a) is a factor of f(x), then f(a) = 0

**Explanation:**

Let f (x) = x^{3}+10x^{2} +mx + n

Since, (x + 2) and (x – 1) are factor of f (x)

So, f (–2) = 0

(–2)^{3} + 10 (–2)^{2} + m (–2) + n

32 – 2m + n = 0 (i)

f (1) = 0

(1)^{3} + 10 (1)^{2} + m (1) + n = 0

11 + m + n = 0 (ii)

(2) – (1)

3m –21 = 0

**m = 7 (iii)**

Using (iii) and (ii), we get

11 + 7 + n= 0

**n = – 18**

*Rate this question :*

*How useful is this solution?We strive to provide quality solutions. Please rate us to serve you better.*

*Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic ExpertsDedicated counsellor for each student24X7 Doubt ResolutionDaily Report CardDetailed Performance Evaluationview all courses*

*RELATED QUESTIONS :*

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x^{31</s}RS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x^{3}RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics